Foam assisted CO2-EOR: A review of concept, challenges, and future prospects - Talebian, S.H. (Elsevier, 2014)
Foam assisted CO2 enhanced oil recovery has attracted increasing attention of oil companies and research institutions, mainly due to the potentially high benefit of foam on CO2-EOR performance. Numerous theoretical and experimental studies, limited numbers of pilot tests as well as cases of field applications have indicated that foaming of CO2 can greatly improve the EOR process, at both the microscopic and macroscopic levels. However, there are still various conceptual and operational challenges, which may compromise the success and application of foaming process.The oil recovery mechanisms involved in a CO2 foam flood, the complex flow behavior of the system, and the synergy between gas mobility control foaming agent and ultra-low IFT surfactants have been identified as the main challenges of this process. The unavailability of reliable predictive tools due to the less understood concepts and phenomena adds more challenges to the process results and application justifications.A literature review of the foam assisted CO2-EOR process is presented in this paper to reveal its strengths, highlight the knowledge gaps, and suggest ways to bring physical understandings of experiments into foam projectsU+05F3 performance evaluation and simulation models for potential field application purposes. Â© 2014 Elsevier B.V.